Aksara Suci dalam Tata Cara Penulisan Kakereb Tapakan Ida Bhatara Ratu Sakti di Pura Dalem Pakenca Desa Gunaksa Kecamatan Dawan Kabupaten Klungkung - ni komang astiti mang asti; Gusti Nyoman Mastini; I Putu Eddy Purnomo Arta (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2026)
This study analyzes the presence of sacred script in the Kakereb Tapakan Ida Bhatara Ratu Sakti inscription at Pura Dalem Pakenca, Gunaksa Village, Klungkung. Kakereb is believed to possess spiritual powers capable of neutralizing negative energy and bad karma in the Great and Alit Bhuanas. The purpose of this study to explore the form, function, and meaning of the Sacred Script using Symbol Theory, Function Theory, and Meaning Theory. The methodology used is a descriptive qualitative approach with a purposive sampling technique. The data obtained consists of primary and secondary data, collected through observation, interviews, literature review, and documentation, which are then analyzed through the processes of data reduction, data presentation, and verification. The research findings show that: (1) The Sacred Script used is categorized as Wijaksara Script, including Eka Aksara to Dasa Aksara, including the symbols of Sang Hyang Achintya and the Weapons of the Gods Nawa Sanga. The writing goes through ritual stages, means and infrastructure, and the use of special mantras. (2) The function of the Sacred Script in Kakereb includes religious, magical, social, and cultural aspects. (3) The meanings contained in the writing procedure are aesthetic and artistic meanings, symbolic meanings, and religious meanings. This research concludes that the Sacred Script in Kakereb plays a significant role as a spiritual medium in preserving the customs and traditions of the Hindu community in Bali.